1992
DOI: 10.1113/jphysiol.1992.sp019006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐mediated regulation of excitation‐contraction coupling in canine gastric smooth muscle.

Abstract: SUMMARY1. Agonists known to increase cyclic AMP levels in gastrointestinal smooth muscles were studied in isolated circular muscles of the canine antrum to investigate the mechanisms of the inhibitory effects of these agents.2. Muscles were electrically active, generating typical slow wave activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
3
25
1
Order By: Relevance
“…ATP-induced relaxation of depolarized VD was correlated with a reduction of the level of PMLC. Most likely this reflected the inhibition of the myosin light chain kinase (MLCK) when it is phosphorylated by a cyclic AMP-dependent protein kinase A (Adelstein et al, 1978;Kerrick & Hoar, 1981;Nishimura & van Bremen, 1989;Ozaki et al, 1992) On the basis of the rank order of potency of different ATP analogues, of the absence of tachyphylaxis and of the action of selective antagonists, it was proposed that ATP-induced relaxation implies a P2Y-like purinoceptor (Boland et al, 1992). Our results suggest that this effect is linked to the activation of adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-induced relaxation of depolarized VD was correlated with a reduction of the level of PMLC. Most likely this reflected the inhibition of the myosin light chain kinase (MLCK) when it is phosphorylated by a cyclic AMP-dependent protein kinase A (Adelstein et al, 1978;Kerrick & Hoar, 1981;Nishimura & van Bremen, 1989;Ozaki et al, 1992) On the basis of the rank order of potency of different ATP analogues, of the absence of tachyphylaxis and of the action of selective antagonists, it was proposed that ATP-induced relaxation implies a P2Y-like purinoceptor (Boland et al, 1992). Our results suggest that this effect is linked to the activation of adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…The agents that increase cyclic AMP (ISO, VIP, CGRP and forskolin) and cyclic GMP (sodium nitroprusside) in gastric muscle produced inhibition of electrical slow waves, Ca" transients, mechanical activ ities and Ca" sensitivity of contractile elements (5,33). Thus, it is possible that not only cyclic AMP but also cyclic GMP may contribute to the inhibitory effects of ISO in taenia.…”
Section: Discussionmentioning
confidence: 99%
“…In other intestinal smooth muscles, cAMP (or db-cAMP) had no effect on the amplitudes of voltage-dependent Ca 2 þ currents generated by L-type Ca 2 þ channels (rabbit jejunum, Ohya et al, 1987;guinea-pig taeniacoli, Muraki et al, 1993). An inhibition of L-type Ca 2 þ channels was proposed in guinea-pig gastric smooth muscle (Ozaki et al, 1992). Several inhibitory agonists that activate adenylate cyclase (such as b-adrenergic stimulators, forskolin, VIP, CGRP, etc.)…”
Section: H-l Zhu Et Almentioning
confidence: 99%
“…were found to decrease the increases in [Ca 2 þ ] i associated with each slow wave and inhibit contraction. Although it was suggested that this might result from an inhibition of Ca 2 þ influx during each slow wave (Ozaki et al, 1992), a direct test of this idea was not attempted.…”
Section: H-l Zhu Et Almentioning
confidence: 99%